Eco-Tourism as a Potential Tool for Biodiversity Conservation and Sustainable Livelihood in Himalayan Region, with Special Reference to Garhwal Region: Examining the Impact of Ecotourism on High Elevation Lakes and Local Communities in the Garhwal Region (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The High height lake has been the focal point of the fascination for tourists since antiquated occasions. After the development of Uttarakhand state, High elevation lakes are pulling in vacationer around the globe. In such a situation, tourism area has become the primary source of economy of Uttarakhand. This paper investigates the Ecotourism, as a reasonable income source for mountain networks that lives around these High height lakes. The present examination was directed on the unmistakable component of tourism in Dodi Tal Lake and its effect on socioeconomic status just as effects on the lake condition in some chose towns, Agoda (s1), Dasda (s2) and Dandalka (s3). The essential information was gathered with the assistance of amass poll and furthermore utilizing secondary information from assorted source. The investigation uncovers that agriculture (91) is unmistakable income source while ecotourism is as second significant income source of these three towns. The ecotourism is being viewed as reasonable source of salary age and seen as entrancing assignment for the adolescent. Ecotourism has averted the young movement in Dodi Tal environ. In spite of agriculture, roughly 85 of the families have their most noteworthy yearly normal salary through tourism exercises. After completely receiving tourism, changes in the conventional expectation for everyday comforts of this territory were taken note. Be that as it may, the tourism rehearses in the Dodi Tal territory has been recognized as a key of natural issues influencing the lake Environment. This discovering recommends that the need of all around arranged and reasonable eco-tourism approach in the locale. This paper supports to make agreement between the mountain network and the high height lake condition.